PENGARUH PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, KAPITALISASI PASAR DAN KEPEMILIKAN SAHAM PUBLIK PADA TINGKAT PENGUNGKAPAN CSR - Indraswari, I Gusti Ayu Laksmi; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2017)
This study aimed to get empirical evidence about the influence of profitability, growth, market capitalization and public ownership on the level of corporate social responsibility disclosure. This research conducted on food and beverage companies listed in Indonesia Stock Exchange in 2012-2015. Sampling method used in this research is nonprobability sampling method with purposive sampling, and total samples obtained 11 companies with 44 observations. The analysis technique used in this research is multiple linear regression analysis. The results showed that profitability and growth has no effect on the level of corporate social responsibility disclosure, market capitalization has positive effect on the level of corporate social responsibility disclosure, public ownership has negative effect on the level of corporate social responsibility disclosure.
Keywords: profitability, growth, market capitalization, public ownership, CSR